2019
DOI: 10.4028/www.scientific.net/kem.796.62
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Erbium Addition on the Microstructure and Mechanical Properties of Aluminium Alloy

Abstract: The effect of rare earth metal erbium (Er) modification on the microstructure and mechanical properties of aluminium alloys (A380) were investigated using Optical Microscope (OM), Scanning Electronic Microscope (SEM) attached with Electron Dispersive Scanning (EDS), Vicker’s hardness test and Ultimate Tensile Test (UTS). The results show that the addition of Er reduces the size of the silicon particle and improve mechanical properties of the aluminium alloy. In addition, by adding 0.1 wt. % of Er, the mean are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Lightweight materials such as aluminum alloys, of which the strength to weight ratio is superior to that of steel, have been widely applied on automotive parts to reduce their weight [1][2][3][4]. However, the surface roughness of aluminum alloy has a significant influence on the performance of mechanical parts as well as production cost [5].…”
Section: Introductionmentioning
confidence: 99%
“…Lightweight materials such as aluminum alloys, of which the strength to weight ratio is superior to that of steel, have been widely applied on automotive parts to reduce their weight [1][2][3][4]. However, the surface roughness of aluminum alloy has a significant influence on the performance of mechanical parts as well as production cost [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Mg-Al alloys, erbium addition has improved purity of the alloy, refined the grains, and exhibited more uniform grain distribution. Overall, mechanical properties were improved [33,34]. Mg-Er alloys were investigated as well, although in larger quantities in terms of atomic composition [32].…”
Section: Introductionmentioning
confidence: 99%
“…Among other materials known from the literature, magnesium-based materials constitute promising alternatives for medical applications, due to their characteristics such as good mechanical and biological properties, corrosion resistance and the reactive ability to interact with other elements. Yet there are not many advanced studies on the influence of Er on the properties of cast magnesium-based alloys in the literature [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…And Tantiwaitayaphan et al [16] also reported that the addition of Er can reduce the degree of subcooling and cause the morphology of eutectic silicon to change. These research show that the rare earth element Er can improve the morphology of the secondary phase and improve the mechanical properties of the aluminum alloys [17][18][19][20][21], but it has not been proposed which kind of particles the Er element will form with the Al-Si alloys to affect the morphology of the secondary phase.…”
Section: Introductionmentioning
confidence: 99%